SEMIQUANTITATIVE DETERMINATION OF TRANS-VACANT AND CIS-VACANT 2:1 LAYERS IN ILLITES AND ILLITE-SMECTITES BY THERMAL ANALYSIS AND X-RAY DIFFRACTION - Drits V.A.; Salyn A.L.; Lindgreen H.; Ylagan R.; McCarty D.K. (My University, 1998)
Interstratified illite-smectites (I/S) and illite-smectite-vermiculites (ISV) representing both hydrothermal and diagenetic transformations and having different degrees of structural order were investigated for cis-trans occupancy in the octahedral sheet by X-ray diffraction (XRD) and by differential thermal analysis (DTA) in combination with evolved water analysis (EWA) using an infrared detector. By XRD, the amounts of cis (wcv) and trans (wtv) vacant 2:1 layers were determined for the three-dimensionally ordered samples using both the WILDFIRE simulation program and calculations based on positions of the 11l and 11 reflections. Based on the EWA curves, the I/S and ISV could be divided into three l groups having (1) one strong and one or more weak EWA peaks; (2) two well-resolved peaks; and (3) a complex EWA curve. The amounts of cis- and trans-vacant sites were determined by peak fitting of the total dehydroxylation curve. The complex EWA curves were, however, in addition split into separate dehydroxylation processes during a step- heating technique. If the EWA peaks below and above 600 8C were attributed to trans vacant (tv) and cis vacant (cv) octahedra, respectively, the wcv values determined by XRD and by EWA were in agreement. For the three-dimensionally ordered minerals, both XRD and EWA should be used, whereas the EWA method can be applied to the structurally disordered samples having no diagnostic 11l reflections. Accordingly, a combination of XRD and EWA for the determination of wcv and wtv supports an evaluation of the mech- anism of illitization in various geological environments. Thus, significant changes in wcv and wtv during illitization are likely due to a dissolution-precipation, whereas almost constant values indicate a solid-state transformation.